2018
DOI: 10.1111/bjdp.12274
|View full text |Cite
|
Sign up to set email alerts
|

The role of in‐group norms and group status in children's and adolescents’ decisions to rectify resource inequalities

Abstract: Children's and adolescents’ resource allocation was examined in a context of inequality between schools and a peer group norm of either equality or equity. Participants (N = 257; children, 7–11 years old and adolescents, 13–16 years old) were inducted into groups with either a lot (advantaged) or few (disadvantaged) art resources, in the context of an art competition. Participants were prescribed an equality (equal distribution) or equity (more resources for disadvantaged groups) norm, before allocating resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
1
41
1
Order By: Relevance
“…This helps them foster positive relationships with peers and gain popularity (Garner and Waajid, 2008;Slaughter et al, 2015). Indeed, recent research has repeatedly demonstrated that when group norms are not consistent with those of social convention, older (but not younger) children tend to give priority to group-specific norms to demonstrate their affiliation (Haun and Tomasello, 2011;Killen et al, 2013;McGuire et al, 2018aMcGuire et al, , 2018b.…”
Section: Children's Conformity To Social Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…This helps them foster positive relationships with peers and gain popularity (Garner and Waajid, 2008;Slaughter et al, 2015). Indeed, recent research has repeatedly demonstrated that when group norms are not consistent with those of social convention, older (but not younger) children tend to give priority to group-specific norms to demonstrate their affiliation (Haun and Tomasello, 2011;Killen et al, 2013;McGuire et al, 2018aMcGuire et al, , 2018b.…”
Section: Children's Conformity To Social Normsmentioning
confidence: 99%
“…This is perhaps because adolescence is a period of development characterized by peer influence (Chein et al, 2011), with adolescents showing heightened sensitivity to positive social cues in the presence of peers (Breiner et al, 2017;Smith et al, 2018). In addition, the motivation to affiliate with peers is considered to develop as children age (Kohlberg, 1971;McGuire et al, 2018aMcGuire et al, , 2018b. Thus, if children's conformity to normative influence is driven by a goal of affiliation, then an injunctive norm indicating the majority of their peers' social approval of healthy eating should have a stronger influence on adolescents than those in middle childhood, affecting both intentions and behaviors (Slaughter et al, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…This suggests that there is further work to be done to determine how important goals and norms are in children's and adolescents' resource allocation outside of experimental manipulations. Further, the coding framework used here was based on existing theory and experimental work (McGuire et al, 2019;Turiel, 1983) but did not achieve strong inter-rater reliability. It will be important for future work to establish the extent to which children and adolescents reference contextual issues in their reasoning justifications outside of these specific experimental manipulations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…We also varied the focus of children’s group concerns by manipulating an in‐group norm. Given research that has demonstrated the importance of competitive and cooperative group norms in intergroup resource allocation decisions (McGuire, Elenbaas, Killen, & Rutland, 2019; McGuire, Rizzo, Killen, & Rutland, 2018), here we asked participants to allocate resources across three goal contexts, while manipulating an in‐group norm of competition or cooperation within each context.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the folk tendency to disapprove of market‐based (utility‐maximizing) economic exchanges (also known as “emporiophobia;” Boyer & Peterson, ) arguably reflects the contrast between impersonal, structural systems to manage the exchanges of resources (using money), and those resource exchanges that are local, personal, and relationship‐based. Both perspectives are fundamental—even young children at times value resource‐maximizing motives, and at times value those that are altruistic (Echelbarger, Gelman, & Kalish, ,b; McGuire, Elenbaas, Killen, & Rutland, ). The key point here is that there is a continuous thread linking foundational human object concepts with concepts of the self, but also that an important task of childhood is to acquire culturally‐specific norms regarding what is appropriate in different contexts (i.e., when to embrace vs. reject market norms).…”
Section: Objects and The Selfmentioning
confidence: 99%